Experimental and theoretical study of long counters on the departure of "point" assumption and scattering background influence. (November 2015) - Wang, Guan-bo; Qian, Da-zhi; Li, Jun-jie; Yang, Xin; Li, Run-dong; Tang, Bin
Abstract: A new long counter has been constructed and calibrated with the inherent efficiency of 11.5 cm 2 in the 2.5 MeV neutron field, and a relative flat energy response of 20% disparity within 0.5 MeV–15 MeV. Using this detector and another commercial DePangher counter, the departure of "point" assumption at near distance and the scattering background influence are investigated by performing three groups of experiments in low, middle and high scattering room. Simulation studies are also performed to supplement the experimental data. Two conclusions are deduced. First, the direct efficiency η is very sensitive when the source is very near, and the departure of point assumption is very evident at this situation. So, a revising method is tried to put forward, employing the on-site calibration with a known neutron source and theoretical calculated coefficient D = (η/ε)/(ηcf252 /εcf252 ). And second, scattering backing counts are found mainly from the nearest wall or scatterers. However, the relatively uniform isotropic scattered neutrons contribute insensitive to the source-detector distance, which means the background tally can be eliminated by some simple ways. Highlights: A new long counter was built and calibrated with a higher and more flat energy response. Monte Carlo simulation is performed for the two kinds of long counter. The (η/ε) r 2 values can be treated as a reference for "point" assumption. The scattering counts are roughly constant and not sensitive to neutron source energy.